A Prediction Method Of Rice Harvesting Using Artificial Neural Network - Fitri Anindyahadi; Imam Much Ibnu Subroto; Arief Marwanto (Journal of Telematics and Informatics, 2020)
Crops rice is a thing he could never expected for sure, but could have predicted data in of existing. The availability of data about the outcome of rice harvesting is very substantial for use as yardstick in estimate and predicts crops rice as a gesture to fix the next planting. Artificial neural network method backpropagation often used to settle trouble complex relating to identification, predictions, pattern recognition and so on. In this study, backpropagation processing the data affecting rice crops from 2014 until 2016 to predict crop Pengkok, Kedawung, Sragen the future. After through process of training and testing and experiment some pattern architecture network, in the network get architecture best in a prediction.